1997
DOI: 10.1111/j.1439-0418.1997.tb01431.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prey mites and pollen on the biology and life tables of Proprioseiopsis asetus (Chant) (Acari, Phytoseiidae)

Abstract: Biology of the phytoseiid mite Proprioseiopsis usetus was studied under laboratory conditions. Egg hatchability was tested at three different combinations of temperature and relative humidity. A combination of 26'C and 70% RH was the most suitable condition. The number of citrus brown mite Eutetranychus orientalis (Klein) consumed by P. asetus adult females significantly decreased when date palm pollen Pheonex dactylefira L. was added to prey mite and egg production significantly increased. Total developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 15 publications
3
15
2
2
Order By: Relevance
“…Similar results were obtained for some other phytoseiids (Badii and McMurtry 1984;Takahashi and Chant 1992). However, Fouly (1997) reported that 26°C with 70% RH was the optimum temperature for P. asetus egg hatch.…”
Section: Model Developmentsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar results were obtained for some other phytoseiids (Badii and McMurtry 1984;Takahashi and Chant 1992). However, Fouly (1997) reported that 26°C with 70% RH was the optimum temperature for P. asetus egg hatch.…”
Section: Model Developmentsupporting
confidence: 84%
“…4). Fouly (1997) reported similar data for P. asetus males and females fed four different phytophagous mite species at 26°C. The range for the sexes at specific life stages across the four host species was egg: 26-38%, larva: 14-18%, protonymph: 22-26% and deutonymph: 25-31%.…”
Section: Model Developmentsupporting
confidence: 57%
See 1 more Smart Citation
“…The intrinsic rate of increase recorded in the current experiment for N. bicaudus at 26 ºC and 35 ºC (0.24 and 0.40, respectively), were considerably higher than the values obtained by Fouly (1997) and Emmert et al (2008) for Proprioseiopsis asetus at 26 ºC and 35 ºC (0.18-0.28 and 0.17-0.32, respectively).…”
Section: Discussioncontrasting
confidence: 81%
“…Gerson et al (2003) afirmaram que os eriofiídeos constituem somente parte da dieta diversifi cada de muitos fi toseídeos, não sendo muito comum a preferência desses predadores por ácaros pertencentes àquela família de ácaros fi tófagos. São poucos os estudos sobre a biologia de Proprioseiopsis Muma (Ball 1980, Abou-Setta et al 1997, Fouly 1997 Brevipalpus phoenicis não se mostrou favorável para permitir o crescimento signifi cativo da população de P. cannaensis. Os valores de R o , r m , e λ foram muito baixos quando esse predador foi alimentado com aquele tipo de alimento.…”
Section: Brevipalpus Phoenicisunclassified